Preparation of Amine‐ and Disulfide‐Containing PAMAM‐Based Dendrons for the Functionalization of Hydroxylated Surfaces: XPS as Structural Sensor. Issue 16 (24th April 2020) - Viltres, Herlys; Odio, Oscar F.; Biesinger, Mark. C.; Montiel, Gala; Borja, Raúl; Reguera, Edilso
Abstract: Herein, we report the synthesis of novel poly(amido amine) [PAMAM]‐based dendrons with external amine and disulfide functional groups and an alkoxysilane moiety as the focal point. Four generations (G1 ‐G4 ) of dendrons were obtained by combining Michael addition and amidation reactions using (3‐aminopropyl) trimethoxysilane as the starting core; disulfide bridges and amine groups were introduced in the last step by ester amidation with cystamine and ethylendiamine. The resulting dendrons were characterized by Thermogravimetric Analysis (TGA), Fourier Transform Infrared (FTIR), Raman, Atomic Force Microscopy (AFM), Dynamic Light Scattering (DLS) and Z‐potential techniques. The growth of the dendrons was monitored by analysing the X‐ray Photoelectron Spectroscopy (XPS) high resolution spectra of the Si 2p, N 1s, C 1s, O 1s and S 2p signals for each dendron generation. The results evidence that it is possible to record, with good confidence, the compositional and structural changes that occur during the preparative route by means of XPS technique. Abstract : Fourth‐generation poly(amido amine) [PAMAM]‐based dendrons are designed with an alkoxysilane moiety as focal point and mixed terminal groups containing amine and disulfide bridges. X‐ray Photoelectron Spectroscopy (XPS) is revealed as a confident tool for monitoring the structural and compositional changes that occur during dendron growth.